Stimuli-Responsive Nanoplatform-Assisted Photodynamic Therapy Against Bacterial Infections - Zhou, You; Deng, Wenmin; Mo, Mulan; Luo, Dexu; Liu, Houhe; Jiang, Yuan; Chen, Wenjie; Xu, Chuanshan (Frontiers in Medicine, 2021)
Bacterial infections are common diseases causing tremendous deaths in clinical settings. It has been a big challenge to human beings because of the antibiotics abuse and newly emerged microbes. Photodynamic therapy (PDT) is a reactive oxygen species (ROS)-based therapeutic technique through light-activated photosensitizer (PS). Recent studies have highlighted the potential of PDT as an alternative method of anti-bacterial treatment for its broad applicability and high efficiency. However, there are some shortcomings due to the low selectivity and specificity of PS. Growing evidence has shown that drug delivery nanoplatforms have unique advantages in enhancing therapeutic efficacy of drugs. Particularly, stimuli-responsive nanoplatforms as a promising delivery system provide great opportunities for the effective delivery of PS. In the present mini-review, we briefly introduced the unique microenvironment in bacterial infection tissues and the application of PDT on bacterial infections. Then we review the stimuli-responsive nanoplatforms (including pH-, enzymes-, redox-, magnetic-, and electric-) used in PDT against bacterial infections. Lastly, some perspectives have also been proposed to further promote the future developments of anti-bacterial PDT.